The Examined Patients Before and After Chemotherapy in the Study Groups (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Along with this, the HEART RATE is one of the leading factors in the pathogenesis of CORONARY HEART DISEASE. The disease is one of the main determinants of myocardial oxygen consumption and is closely related to the duration of diastole. Data from numerous authors claim that with a decrease in the severity of ta chycardia, myocardial perfusion improves duye to elongation of the diastole of the left ventricle.